Equilibrium approach towards water resource management and pollution control in coal chemical industrial park. (1st August 2018) - Xu, Jiuping; Hou, Shuhua; Xie, Heping; Lv, Chengwei; Yao, Liming
Abstract: In this study, an integrated water and waste load allocation model is proposed to assist decision makers in better understanding the trade-offs between economic growth, resource utilization, and environmental protection of coal chemical industries which characteristically have high water consumption and pollution. In the decision framework, decision makers in a same park, each of whom have different goals and preferences, work together to seek a collective benefit. Similar to a Stackelberg-Nash game, the proposed approach illuminates the decision making interrelationships and involves in the conflict coordination between the park authority and the individual coal chemical company stockholders. In the proposed method, to response to climate change and other uncertainties, a risk assessment tool, Conditional Value-at-Risk (CVaR) and uncertainties through reflecting parameters and coefficients using probability and fuzzy set theory are integrated in the modeling process. Then a case study from Yuheng coal chemical park is presented to demonstrate the practicality and efficiency of the optimization model. To reasonable search the potential consequences of different responses to water and waste load allocation strategies, a number of scenario results considering environmental uncertainty and decision maker' attitudes are examined to explore the tradeoffs between economic development and environmental protection and decision makers' objectives. The results are helpful for decision/police makers to adjust current strategies adapting for current changes. Based on the scenario analyses and discussion, some propositions and operational policies are given and sensitive adaptation strategies are presented to support the efficient, balanced and sustainable development of coal chemical industrial parks. Highlights: An integrated water and waste load allocation model is built to support water resource and environmental management. Industry Ecology was applied to improve water utilization efficiency and minimize pollution emissions. The trade-offs between economic growth and environmental protection and the two level decision makers were analyzed. A case study is adopted for illustrating applicability of the proposed equilibrium approach. Results can support water and waste load allocation strategies adapting to environmental changes.